Fibromyalgia: development of symptoms and principles of therapy - Gyuzel Rafkatovna Tabeyeva (Неврология, нейропсихиатрия, психосоматика, 2012)
Fibromyalgia is one of the most complex problems of clinical practice. Despite its high prevalence rates in the population and high medical visit rates, fibromyalgia is maldiagnosed. Its clinical symptom development, nosological independence, and the choice of priority treatments are debatable questions. By now the number of randomized trials dealing with the efficiency of treatment for fibromyalgia has substantially increased. This permits the identification of its treatment priorities.